When reality and fantasy merged: A magical realism perspective in A Kiss for Cinderella - Rahma Fitria Nurfaizah; Elisabeth Edlin Talianingrum; Diamonda Naomi Robbani (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2025)
A Kiss for Cinderella is a literary work whose narrative combines elements of reality and fantasy, reflecting the characteristics of magical realism. Magical realism is essential in "A Kiss for Cinderella," as it intertwines reality and fantasy, making the extraordinary feel ordinary. The narrative centers on a young woman enduring difficulty, who finds solace in a dreamlike realm inspired by the Cinderella fairy tale. The novel tells the story of a young woman who experiences hardship while escaping to a dream world inspired by the fairy tale of Cinderella. Through the dream world that she creates, she not only escapes from the harsh reality, but also builds an inner space where she finds meaning, magnificence, and the strength to survive. This study is conducted by reading carefully and thoroughly to the text, and then begin to isolate the part which shows how magical realism exists in the text of the play. This study also highlights how the fusion of real and imagined elements deepens the emotional and thematic impact of the play. This article explores how the interaction between imagination and reality shapes the story's themes and character development. By analyzing key scenes, we examine how magical realism is used to blur the boundaries between the protagonist's struggles and her fantasies. By using this approach, it is hoped to be able to deeply reveal how magical realism plays an important role and is able to strengthen the messages and human values which are contained in the play.